BREAKFAST CONSUMPTION AND BODY MASS INDEX AMONG PRESCHOOLERS IN KUANTAN, PAHANG - Mohamed Anuar, Nur Afifa Natasha; Mohd Shukri, Nor Azwani (International Journal of Allied Health Sciences, 2022)
Introduction: Eating patterns such as eating outside frequently and skipping breakfast are among the contributing factors for obesity. This study aimed to describe the breakfast consumption patterns and associate it with the body mass index (BMI) values among preschoolers in Kuantan, Pahang. In addition, the foods and beverages typically consumed by them during breakfast were also described. Methods: A total of 147 children aged 4-6 years were recruited using convenient sampling. Their BMI values were determined based on measured height and weight. The frequency of breakfast consumption and typical foods and beverages taken were assessed using a self-administered questionnaire completed by parents. Results: About half of the study participants had normal BMI, while 12.2% were either overweight or obese. A total of 57.1% of the preschoolers consumed breakfast at home almost daily, 3-4 times/week (26.5%) and 0-2 times/week (16.3%). Those who ate breakfast at home 3-4 times/week were found to have significantly lower mean BMI compared to those who rarely or never did so (14.1±1.4 kg/m2 vs. 15.7±3.2 kg/m2, p-value=0.022). The breakfast foods typically consumed by preschoolers in this study were nasi lemak, fried rice/mee/beehoon/kuey teow, or white bread with spreads. Most of them reported taking malted drinks added with condensed milk for breakfast. Conclusions: Infrequent breakfast consumption at home may be associated with a higher BMI among preschoolers. Intake of fatty and sugary foods/beverages during breakfast may also lead to excess energy intake. Eating a healthy and nutritious breakfast at home is strongly recommended among these preschoolers.